Pengaruh suhu terhadap daya tetas telur ikan kakap putih (lates calcarifer) - rusna benedikta hasibuan; henky irawan; tri yulianto (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2018)
The effect of temperature on hatchedof seabassegg. Tanjungpinang. Aquaculture department. Faculty of marine and fishery. Raja ali haji maritime university. Supervisor Henky irawan and tri yulianto.The effect of temperature was a parameter had been given on lates calcarifer’s egg. The purpose of this research was to knew effect of temperature on hatched ofseabass egg. The research were used completely Random Design (CRD) there was A (28oC), B (30oC), C (32oC), D (34oC). The result showed that a D treatment had the best hatching rate was 44,67%, developing embryo rate was 87413.33% and abnormality was 2,33%.